LUYT, O.L.P. [ Louis] Inventory of documents - LUYT, O.L.P. [ Louis] (ARCA, 2018)
Private papers of O.L.P. Luyt, MP Federal Alliance. Director of several companies, eg. Triomf Fertilizer Investments, Louis Luyt Investments, Louis Luyt Breweries, etc. Best known for his role in S.A. rugby.
COVERAGE 1966-1972; 3 Files; 0.11 metre
Keywords: LUYT, O.L.P. [ Louis]; Triomf Fertilizer